Lighting fires from fires: A description of the research entitled 'kindling fires'. - Kilpert, Leigh (The IIE, 2014)
This study examined students’ responses to assessment for evidence of cumulative learning. The hypothesis was that if students’ learning is cumulative, then they will be able to apply their knowledge and skills productively in industry. The research used Maton’s (2009) concept of ‘semantic gravity’ as a tool to determine the relative context-dependency of the students’ knowledge. A higher education institution provided the Journalism curriculum for this research. Assessments were coded according to ‘knowledge principles’ described by the research tool. The coding allowed these responses to be given a ‘weight’ of semantic gravity, i.e. a level of context-dependency. The codes were then examined for patterns that would reveal evidence of cumulative learning. The study found evidence of cumulative learning, but because of certain limitations, this learning was not fully developed. The findings of this research have implications for an enriched understanding of the potential for students to be productive after they graduate. The mind is not a vessel to be filled but a fire to be kindled. Plutarch (c.46–119 AD)
Keywords: Cumulative learning; Maton; Semantic gravity; Segmented learning; Journalism; Educational knowledge